Efektivitas Tiga Isolat Trichoderma Sp. Asal Pasang Surut Dalam Mengendalikan Penyakit Moler Fusarium Oxysporum F.Sp Cepae Pada Bawang Merah (Allium Ascalonicum L.) - Akhmad Kamal Surya Bakti; Salamiah; Noor Aidawati (Rawa Sains: Jurnal Sains STIPER Amuntai, 2022)
Moler disease in red onion caused by Fusarium oxysporum f.sp cepae is a very dangerous disease because of its fast attack, causing plant death and resulting in crop failure. Disease control itself has various ways, namely using plant-based pesticides, biological agents, and chemicals. An alternative way of controlling moler disease is using the biological agent Trichoderma sp to reduce the risk of using chemicals. The purpose of this study was to determine the ability of three Trichoderma sp. isolates. origin of tidal swamp land in controlling moler disease in red onion. The study used a completely randomized design consisting of 6 treatments and 4 replications, resulting in 24 experimental units. The treatment consisted of T0 without Trichoderma and without Fusarium inoculation, T1 without Trichoderma and Fusarium inoculation, T2a Control using Benlate and Fusarium fungicide, T3 Trichoderma from Kaladan isolate, Kab. Tapin and Fusarium, T4 Trichoderma from runway Ulin and Fusarium isolates, T5 Trichoderma from Barambai isolate, Kab. Barito Kuala and Fusarium. The results showed that Trichoderma sp. able to suppress Fusarium wilt attack on red onion plants The highest attack intensity was found in the control treatment, namely plants inoculated with Fusarium oxysporum with a value of 100%, while onion red plants treated with Trichoderma sp. able to withstand F. oxysporum attack with an attack intensity of 0. Three isolates of Trichoderma sp. namely from Kaladan, Anvil Ulin and Barambai, effectively controlling onion red moler disease caused by Fusarium oxysporum f.sp.